Priming Behavioral Control Enhances Sharing in Preschoolers - Lee, Chanmi; Song, Hyun-joo (Frontiers in Psychology, 2022)
Although young children demonstrate knowledge of fairness norms, their actual sharing is often inconsistent with their understanding. A possible explanation for this discrepancy is the failure of behavioral control in young children. Thus, the present research manipulated behavioral control experimentally and examined its effect on the sharing behavior in 3- to 4-year-olds (N = 64). Children were randomly assigned to either the behavioral control or the neutral prime conditions. In the behavioral control prime condition, the children listened to a story in which a protagonist exerted behavioral control actively, refraining from eating candies. In the neutral prime condition, the children listened to a story in which a protagonist did not explicitly engage in behavioral control. The children then participated in the dictator game. The experimenter asked the children to share as many stickers as they wanted or should with an anonymous child. Children in the behavioral control prime condition shared more stickers than those in the neutral prime condition. However, the two groups did not differ in their judgments of fairness and emotional experiences. The current research provides evidence that preschoolers’ sharing behaviors can be facilitated by behavioral control.